The Association of Upper Body Obesity with Insulin Resistance in the Newfoundland Population - Sherif Youssef; Matthew Nelder; Guang Sun (International Journal of Environmental Research and Public Health, 2021)
Body-fat distribution is a primary risk factor for insulin resistance and cardiovascular disease. Visceral fat explains only a portion of this risk. The link between upper-body fat and insulin resistance is uncertain. Furthermore, upper-body fat is not clearly defined. Dual-energy X-ray absorptiometry (DXA) can accurately quantify body fat. In this study, we explored the relationship between non-visceral upper-body adiposity and insulin resistance and other markers of metabolic syndrome. Fat proportions in the upper body, leg, and visceral regions were quantified by using DXA in 2547 adult Newfoundlanders aged 19 and older. Adjusting for remaining fat regions, we performed partial correlation analysis for each body region and insulin resistance defined by the Homeostatic Model of Assessment (HOMA). Similarly, partial correlation analysis was also performed between each fat region and other markers of metabolic syndrome, including high-density lipoprotein cholesterol (HDL), triglycerides (TG), body mass index (BMI), and blood pressure. Major confounding factors, including age, caloric intake, and physical activity, were statistically controlled by using partial correlation analysis. Interactions between sex, menopausal status, and medication status were also tested. Arm adiposity was correlated with HOMA-IR (R = 0.132, p < 0.001) and HOMA-β (R = 0.134, p < 0.001). Visceral adiposity was correlated with HOMA-IR (R = 0.230, p < 0.001) and HOMA-β (R = 0.160, p < 0.001). No significant correlation between non-visceral trunk adiposity and insulin resistance was found. Non-visceral trunk adiposity was negatively correlated with HDL in men (R = −0.110, p < 0.001) and women (R = −0.117, p < 0.001). Non-visceral trunk adiposity was correlated with TG (total: R = 0.079, p < 0.001; men: R = 0.105, p = 0.012; women: R = 0.078, p = 0.001). In menopausal women, leg adiposity was negatively correlated with HOMA-IR (R = −0.196, p < 0.001) and HOMA-β (R = −0.101, p = 0.012). Upper-body adiposity in the ...